Comparison study between four poles and two poles magnets structure in the hybrid vibration energy harvester - Ab Rahman, Mohd Fauzi; Kok, Swee Leong; Ruslan, Eliyana; Dahalan, Abdul Halim; Salam, Saifullah (2013)
Vibration energy harvester is receiving considerably amount of interest for the past decade. Many improvements such as making it tunable, broadband based and hybrid harvester have been demonstrated in the literature, generally to exploit more electrical energy from the ambient. In this paper, we study the arrangements of the magnets that referred to as cantilever beam proof mass, as means for generating greater electrical power output. The harvesters consist of piezoelectric cantilever beam with two different arrangements of magnets; two poles magnets and four poles magnets attached to its free end tip. A coil is placed underneath the magnets arrangement, so that when the harvester is being excited by external vibration, both piezoelectric and electromagnetic transducer would generate electrical energy. In this paper, a comparison study in terms of generated voltage output, induced current and generated electrical power output are presented. Experimental results show that, the new approach; four pole magnets type harvester is capable of generating greater electrical power as compared to the conventional approach; two pole magnets type harvester, when exposed to its resonant frequency at 1g acceleration ( 1g = 9.8 ms-2 ) . This implies that by incorporating a proper magnets arrangement, the harvester is capable of producing greater power output.